Impact of status cues in computer-mediated communication on perceptions of online political discussions. - Lim, Corinne Xian-Li. (2008)
An experiment design was employed in the investigation of the impact of two status cues, language style and source expertise, on people's perceptions of online political discussants, and their intentions and motivations to participate in local online political discussion fora.